Influence of sleep disturbances on temporomandibular disorders, somatic, and negative emotional symptoms in young adults: A cross-sectional study - Marpaung, Carolina Carolina Marpaung; Dewi, Ni Luh; Pragustine, Yenny; Hanin, Isya; Yuliasari, Hani; rahmadini, Enrita dian (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
Introduction: While temporomandibular disorders (TMDs), sleep disturbances, and psycho-emotional symptoms are interrelated, it remains unclear whether sleep disturbances are a contributing factor to TMDs or a result of chronic pain and somatic symptoms. The objective of this study was to analyze the influence of sleep disturbances on TMD, somatic, and negative emotional symptoms in young adults. Methods: A cross-sectional study was conducted on young adults from a private university in Indonesia. Sleep disturbances were assessed using the Pittsburgh Sleep Quality Index (PSQI), TMD symptoms using the quintessential five TMD symptoms (5Ts), and somatic symptoms using the Patient Health Questionnaire-15 (PHQ-15). Psychological distress and coping strategies were measured using the Depression, Anxiety, Stress Scales-21 (DASS-21) and the Brief Coping Orientation to Problems Experienced Inventory (Brief-COPE). Data were analyzed using the Chi-square test, Kruskal-Wallis, Spearman correlation, and logistic regression (p=0.05). Results: Among the 456 participants (mean age 22.4 ± 1.5 years), 58.2% reported TMD symptoms. Participants with high sleep disturbance had significantly higher TMD pain, somatic symptoms, dysfunctional coping, and psychological distress compared to those with low sleep disturbance. Somatic symptoms and dysfunctional coping were moderately correlated with general distress, anxiety, and stress. Multivariate analyses indicated that the odds of sleep disturbance was increased by somatic symptoms (OR=1.18;95% CI=1.12-1.24) and stress (OR=1.10;95% CI=1.04-1.17). Conclusion: Sleep disturbances are not only linked to TMD but also contribute to increasing the severity of somatic symptoms and psycho-emotional symptoms. Pengaruh gangguan tidur terhadap gangguan temporomandibula, somatik, dan gejala emosional negatif pada dewasa muda: sebuah studi potong lintangPendahuluan: Gangguan temporomandibular (TMD), gangguan tidur, dan gejala psiko-emosional saling berkaitan, namun masih belum jelas apakah gangguan tidur merupakan faktor yang berkontribusi terhadap TMD atau justru merupakan akibat dari nyeri kronis dan gejala somatik. Tujuan dari penelitian ini adalah menganalisis pengaruh gangguan tidur terhadap gangguan temporomandibula, somatik, dan gejala emosional negative pada dewasa muda. Metode: Partisipan dari studi potong lintang ini merupakan dewasa muda yang direkrut dari sebuah universitas swasta di Indonesia. Gangguan tidur dinilai menggunakan Pittsburgh Sleep Quality Index (PSQI), gejala TMD dengan lima gejala utama TMD (5Ts), dan gejala somatik menggunakan Patient Health Questionnaire-15 (PHQ-15). Tekanan psikologis dan strategi koping diukur menggunakan Depression, Anxiety, Stress Scales-21 (DASS-21) dan Brief Coping Orientation to Problems Experienced Inventory (Brief-COPE). Analisis data dilakukan dengan uji Chi-square, Kruskal-Wallis, korelasi Spearman, dan regresi logistik (α=0,05). Hasil: Sebanyak 58,2% dari 456 partisipan melaporkan mengalami gejala TMD (usia rata-rata 22,4 ± 1,5 tahun). Partisipan dengan tingkat gangguan tidur yang tinggi menunjukkan tingkat nyeri TMD, gejala somatik, koping disfungsional, dan tekanan psikologis yang secara signifikan lebih tinggi dibandingkan dengan mereka yang memiliki gangguan tidur rendah. Gejala somatik dan koping disfungsional menunjukkan korelasi sedang dengan tekanan psikologis umum, kecemasan, dan stres. Analisis multivariat menunjukkan bahwa kemungkinan terjadinya gangguan tidur meningkat seiring dengan meningkatnya gejala somatik (OR = 1,18; 95% CI = 1,12–1,24) dan stres (OR = 1,10; 95% CI = 1,04–1,17). Simpulan: Gangguan tidur tidak hanya berkaitan dengan TMD, tetapi juga berkontribusi terhadap peningkatan keparahan gejala somatik dan psiko-emosional.